2006
DOI: 10.3354/meps323001
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed–herbivore interactions at a small scale: direct tests of feeding deterrence by filamentous algae

Abstract: High growth rates and temporal or spatial opportunism are considered central to the success of filamentous algae, in particular for escaping or minimising the effects of herbivory. However, the role of chemical defences in filamentous algae has received far less attention. We investigated possible chemical feeding deterrence by filamentous red algae that have conspicuous cellular inclusions (Asparagopsis armata, Anotrichium tenue and Balliella amphiglanda) and 2 others without inclusions (Callithamnion korfens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…Generalist and mobile species of the genus Hyale in Australasia usually preferred Ulva to several other macroalgae, including its host seaweed (Taylor and Steinberg 2005). Likewise, Ulva was shown to be the preferred food item for other vagile amphipod species (including H. nigra) in no-or multi-choice feeding assays (Kraufvelin et al 2006;Paul et al 2006). H. nigra was shown to consume Ulva sp.…”
Section: The Role Of Consumers In Controlling Vegetated Soft-bottom Cmentioning
confidence: 98%
“…Generalist and mobile species of the genus Hyale in Australasia usually preferred Ulva to several other macroalgae, including its host seaweed (Taylor and Steinberg 2005). Likewise, Ulva was shown to be the preferred food item for other vagile amphipod species (including H. nigra) in no-or multi-choice feeding assays (Kraufvelin et al 2006;Paul et al 2006). H. nigra was shown to consume Ulva sp.…”
Section: The Role Of Consumers In Controlling Vegetated Soft-bottom Cmentioning
confidence: 98%
“…Hay et al (1994) showed that Cymadusa filosa was abundant in some green algae from the Florida Keys but was deterred by chemical defenses and/or calcification from Udotea, Penicillus and Rhipocephalus. Paul et al (2006) studied the consumption of filamentous algae with and without cellular inclusions by Hyale nigra. Alhtough these studies pointed out important aspects of herbivory by ampithoid and hyalid amphipods, the role of Sargassum and its epiphytic algae in the distribution and feeding of herbivorous amphipods in tropical algal beds are still poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study conducted with A. armata demonstrated that an increase in toxicity towards bacteria was related to the amount of bioactive halogenated compounds (Paul et al 2006a). The halogenation process was also shown determinant for the deterrence of non-specialized herbivores (Paul (Paul et al 2006b;Rogers et al 2003;Vergés et al 2008) and the abalone Haliotis rubra (Paul et al 2006b;Shepherd andSteinberg 1992 in Paul 2006) are known to graze A. armata, and only the sea hare Aplysia fasciata was reported to feed on A. taxiformis (Altamirano et al 2008). Competition for space might also promote defensive traits as macroalgae can be abundant in temperate infralittoral zones (Mineur et al 2015;Vermeij 1978).…”
Section: Relationship Between Metabotypes and Bioactivitiesmentioning
confidence: 99%
“…The genus Asparagopsis is known to biosynthesize about one hundred of halogenated volatile hydrocarbons containing one to four carbons with antimicrobial, antifeedant and cytotoxic properties (Genovese et al 2012;Kladi et al 2004;Paul et al 2006b). Assessment of resources allocated to defense traits can be obtained through analysis of the specialized metabolism using metabolomics.…”
Section: Introductionmentioning
confidence: 99%